The influence of principals' visionary leadership and affective commitment on principal performance in senior high schools and vocational high schools in South Labuhanbatu Regency - Anni Zhofatul Fikriah; Aziddin Harahap; Marlina Siregar; Junita Junita; Muhammad Ardansyah (Lembaga Riset Mutiara Akbar, 2026)
This study aims to analyze the influence of principals' visionary leadership and affective commitment on their performance, both individually and simultaneously. A quantitative research approach employing path analysis was used to examine the relationships among the research variables. The study involved 44 principals of senior high schools (SMA) and vocational high schools (SMK) in South Labuhanbatu Regency. Data were collected using validated and reliable research instruments and analyzed to determine the direct and combined effects of the independent variables on principals' performance. The findings reveal that visionary leadership has a positive and significant influence on principals' performance, with a path coefficient of 0.644. Affective commitment also demonstrates a positive and significant influence, with a path coefficient of 0.684. Furthermore, visionary leadership and affective commitment simultaneously have a positive and significant effect on principals' performance, with a combined coefficient of 0.750. These findings suggest that strengthening principals' visionary leadership and affective commitment is essential for improving leadership effectiveness and overall school performance.